I know I can do long division to find it, and once I get to the form mx+b, that's the slant asymptote lol
how far did you get with the long division?
Not very lol my mind went blank
Is there an easier way?
we could use synthetic division if you want?
write out the coefficients in a horizontal line |dw:1444259096702:dw|
|dw:1444259093792:dw| I don't remember if we put -3 or 3 outside though...
solve x+3 = 0 for x to get x = 3 so -3 is our test root |dw:1444259144243:dw|
I remember this now...
oops, I meant to say `to get x = -3`
so our equation would be x-3...
er...y=x-3, my bad
yep the slant asymptote is `y = x-3`
Thank you! :)